A 10- or 14-day Bismuth-containing Quadruple Therapy as a First-line Helicobacter pylori Eradication Therapy: A Systematic Review and Meta-analysis - Sung Eun Kim; Hye-Kyung Jung; Seung Joo Kang; Yong Chan Lee; Hyo-Joon Yang; Seon-Young Park; Cheol Min Shin; Hyun Chul Lim; Jie-Hyun Kim; Su Youn Nam; Woon Geon Shin; Jae Myung Park; et al. (Yong Chan Lee, 2021)
Background/Aims The eradication rate of the first-line standard triple therapy (STT) for Helicobacter pylori (H. pylori) infection has decreased since 2000; therefore, other first-line therapies are required. This study was aimed at investigating the efficacy of bismuth-containing quadruple therapy (PBMT) for first-line H. pylori eradication compared to STT, sequential therapy (SQT), and concomitant therapy (CT). Materials and Methods The Ovid-MEDLINE, Koreamed, EMBASE, KMBASE, and Cochrane Library databases were searched from January 2008 to July 2018. All identified randomized controlled trials (RCTs) comparing PBMT and non-PBMT for first-line H. pylori eradication therapy were included in the final analysis. Results A total of 3,653 patients from seven RCTs were enrolled. The pooled eradication rates of PBMT by intention-to-treat (ITT) and per-protocol (PP) analyses were 82.1% (95% CI, 68.2~90.8%) and 88.8% (95% CI, 77.1~94.9%), respectively. However, no statistically significant difference was observed in eradication rates of the 10- or 14-day PBMT as compared to 14-day STT, 10-day SQT, and 10-day CT in ITT and PP analyses. PBMT was significantly higher in adverse events than in the other eradication regimens (RR, 1.64; 95% CI, 1.11~2.44). Considerable heterogeneity in adverse events was observed among studies (χ2=88.7; P<0.001, I2=93%). Conclusions PBMT can be the first-line treatment for H. pylori eradication in Korea when other first-line options, including STT, SQT, or CT, are unavailable due to their high adverse event rates.